From political sports to sports politics: on political mobilization of sports issues. Issue 4 (2nd October 2018) - Seippel, Ørnulf; Dalen, Håvard B.; Sandvik, Morten R.; Solstad, Gerd Marie
ABSTRACT: How and why do sports issues turn into politics? The aim of this paper is to explore how politicization of sports might happen, to show how social movement theory might contribute to such understandings and to contribute to a theoretical understanding of the political mobilization of sports issues. To achieve this aim, we outline a three-dimensional theoretical framework based on social movement theory. Thereafter we present six cases of more-or-less contested sports issues: gender, sexuality, doping, extreme wages, boxing/violence and failed talent development. Finally, we discuss the main features of our theoretical framework in light of these cases. How do political opportunity structures contribute to political mobilization of sports issues? How do cultural factors make a difference in political processes concerning sports? Which actors are involved when contested sports issues occur? The aim of this exploration is to discover how various societal factors addressed in our theoretical framework matter relative to how and why sports issues might turn into politics.